Unsplit field implicit PML algorithm for complex envelope dispersive LOD-FDTD simulations - Ramadan, O. (Institution Engineering Technology-Iet, 2007)
Complex envelope locally one-dimensional (LOD) perfectly matched layer (PML) formulations are presented for truncating dispersive finite-difference time-domain (FDTD) simulations. The formulations are free from the Courant Friedrich Levy stability limit of the explicit FDTD algorithm. A numerical example carried out in two-dimensional linear Lorentz dispersive domain shows that the proposed formulations perform better than the classical LOD PML formulations.
Keywords: Media